Optimizing stand structure for trade‐offs between overstory timber production and understory plant diversity: A case‐study of a larch plantation in northwest China. (12th July 2018) - Ahmad, Bilal; Wang, Yanhui; Hao, Jia; Liu, Yanhui; Bohnett, Eve; Zhang, Kebin
Abstract: Trade‐offs are often required for an optimal and sustainable supply of competing services from forests. A study was conducted in northwest China to explore a practical trade‐off approach, for promoting the rehabilitation of service‐degraded plantation, focusing on the two main competing services of timber production and understory plant diversity conservation (expressed by understory vegetation species number [UVSN]). To describe the stand structure parameter variation with age and tree density, the logistic growth model and power function were coupled and fit with field data from 82 plots of larch ( Larix principis‐rupprechetii Mayr) plantation within the estimated age range of 12–33 years. The UVSN variation with canopy density and tree density were also quantified. These models and relations developed can serve as a tool for estimating trade‐offs. The results showed that with rising tree density, the single tree timber volume decreased but the stand timber volume increased. The UVSN increased until its maximum, at the canopy density range of 0.6–0.7, and then decreased quickly. A proper tree density corresponding to the optimal canopy density of around 0.7 should be kept for maintaining higher UVSN and adequate timber production. In case of the larch plantation studied, optimal tree densities were found around 2, 600, 2, 000, 1, 600, 1, 250, and 1, 000 trees/ha for the ages of 15, 20, 25, 30, and 35 years, respectively. Although only two main services were considered, the trade‐off approach developed here can be a reference for future studies to guide the rehabilitation and multifunctional management of service‐degraded plantation.